1998
DOI: 10.1164/ajrccm.157.2.9703070
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Elastase and α1-Antitrypsin in Sputum of Asthmatic Patients

Abstract: Asthma and chronic bronchitis are inflammatory diseases associated with remodeling of the extracellular matrix (ECM). Elastin, a major component of the ECM in the airways, has been previously found to be disrupted in asthma and chronic bronchitis. This study was aimed at evaluating whether elastin disruption might be associated with an imbalance between elastase (active and total) and alpha1-proteinase inhibitor (alpha1-PI), the main inhibitor of elastase. We measured elastase and alpha1-PI in induced sputum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1
7

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 29 publications
4
91
1
7
Order By: Relevance
“…The concentration of neutrophil elastase within the airway lumen is also increased in severe asthma, even when there is no detectable airway infection present (2)(3)(4). An increase in neutrophil elastase is also detected in the airways in chronic bronchitis and in COPD (3,39). The same is the case for cystic fibrosis and ARDS (17,19,40).…”
Section: Pathogenetic Potential Of Neutrophilsmentioning
confidence: 87%
See 2 more Smart Citations
“…The concentration of neutrophil elastase within the airway lumen is also increased in severe asthma, even when there is no detectable airway infection present (2)(3)(4). An increase in neutrophil elastase is also detected in the airways in chronic bronchitis and in COPD (3,39). The same is the case for cystic fibrosis and ARDS (17,19,40).…”
Section: Pathogenetic Potential Of Neutrophilsmentioning
confidence: 87%
“…There is evidence from clinical studies that an exaggerated recruitment and activation of neutrophilic granulocytes in the airways is linked to the clinical course of several inflammatory diseases in the airways and lungs, such as asthma (1)(2)(3)(4)(5)(6)82), nonspecific bronchial hyperreactivity (BHR) (7), chronic bronchitis (3,(8)(9)(10), chronic obstructive pulmonary disease (COPD) (3,(11)(12)(13), cystic fibrosis (14)(15)(16)(17), and acute respiratory distress syndrome (18)(19)(20). The referred evidence has been gathered analysing cellular contents in bronchial tissue, in bronchoalveolar lavage (BAL) fluid, in bronchial biopsies, in induced sputum and in peripheral blood.…”
Section: Neutrophilic Airway Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…BOUSQUET et al [60] reported that biopsy samples from asthmatics showed altered elastin staining. In addition, VIGNOLA et al [61] showed that the enzyme responsible for elastin degradation, elastase, was increased in sputum samples from asthmatics compared with healthy controls. Apart from elastin degradation, it is proposed that neutrophil elastase can also act as a smooth muscle mitogen [62] and promotes mucin gene expression by cleavage of EGF receptor ligands [63].…”
Section: Increased Deposition Of Extracellular Matrixmentioning
confidence: 99%
“…They release enzymes, including extracellular matrix-degrading proteases, elastase, cytokines, and reactive oxygen species, which have been implicated in lung injury (3). The reported effects of reactive oxygen species in asthma include a decrease of betaadrenergic function in lungs, airway smooth muscle contraction, increased vascular permeability, bronchial hyperresponsiveness, increased mucus secretion, impaired ciliary activity, generation of chemotactic factors, lipid peroxidation, and secondary production of mediators with a bronchoconstrictor effect (4,5).…”
Section: Introductionmentioning
confidence: 99%